Sizonqoba! : outliving AIDS in Southern Africa - Ngcaweni, Busani (Africa Institute of South Africa, 2016)
"The aim of this book is to better understand the phenomenon of HIV in a country that has faced the fullest might of the disease and yet, after first faltering, has made more progress than any other country in the world in its response to HIV. It aims to reflect the complexity of this narrative and the range of widely differing insights by featuring what is likely the largest number of contributors in a single publication on the subject in South Africa, as well as a full spectrum of specialised areas, ranging from high-end science to personal reflections."--